The ethics of biotechnology - Sims, Tracey D; Gold, Gayle Friedman; Orhnberger, Jeanne; Forgey, Bob; Hill, Elliott; Athey, Brian; Baker, James; Fleck, Len; Kleff, Susanne; Morris, Jonathan,|cPhD (Biotechnology in the 21st century, 2009)
A group of experts discuss the ethical and moral implications of biotechnology in the twenty-first century